(untitled) (Research, Society and Development, 2023)
The reconversion of an original recipe is a natural practice in cultures where any ingredient or recipe comes into contact, mainly in the eating habits of the Portuguese sugarcane colonies. An example of this cultural practice is the sponge cake, which has been reinterpreted in Japan as “Castell Cake” and “Japanese Cheesecake”. In this research, the traditional Lusitanian version and the two reconverted versions of the sponge cake in Japan were made, later a sensory test was carried out consisting of an acceptability and purchase intention test, among the 3 versions of cakes. The 40 test participants completed an evaluation form containing a test of acceptability and purchase intention, using a response form with a 9-point structured hedonic scale and a 5-point structured attitude scale. The acceptability test showed that the three cake samples had different sensory profiles in texture, aroma, flavor and color attributes, and in most of these attributes the reconverted cakes did not differ statistically from each other, but from the lusitano cake. Regarding the attitude scale, it can be seen that in the sensory test, Japanese Cheesecake and Bolo Castella were the ones of choice as purchase intention, with 45% and 30%, respectively, followed by Bolo de Pão de Ló with only 10 %. This information confirms how the gastronomic reconversion in consumption practice is a cultural action in the search for approximation of values and symbols of belonging.